2019
DOI: 10.6002/ect.2017.0154
|View full text |Cite
|
Sign up to set email alerts
|

Management of Plasma Cell-Rich Acute Rejection in Living-Related Kidney Transplant: Role of Proteasome Inhibitor

Abstract: Bortezomib-based treatment was successful in reverting plasma cell-rich acute rejection and stabilizing graft function, with graft survival of 90% at 2 years. Further studies with large cohorts and randomized trials with or without bortezomib will help in better evaluation of its efficacy, safety, and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In fact, the mean serum creatinine concentration after 12 and 24 months was just about optimal. Of note, the previously reported kidney graft outcomes after the refractory AMR treatment were noticeably worse [7,9,13,14], with several graft losses and suboptimal kidney graft excretory function. We can only hypothesize that some specific properties of bortezomib may condition its effect in the early AMR.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, the mean serum creatinine concentration after 12 and 24 months was just about optimal. Of note, the previously reported kidney graft outcomes after the refractory AMR treatment were noticeably worse [7,9,13,14], with several graft losses and suboptimal kidney graft excretory function. We can only hypothesize that some specific properties of bortezomib may condition its effect in the early AMR.…”
Section: Discussionmentioning
confidence: 85%
“…In some reports, such an adjuvant therapy was effective in decreasing DSAs and stabilizing kidney graft function in mid-term observation [7,9]. Nonetheless, the rate of graft loss during longer follow-up periods was high and the excretory function of still-functioning transplanted organs was markedly decreased [7,9,13,14]. As early as 2010, Walsh et al reported the first use of bortezomib along with a single dose of rituximab in two patients as a primary therapy in early post-transplant AMR, with a rapid DSAs elimination and excellent renal function at five and six months of observation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al reported that they treated with PCAR patients with methylprednisolone (500 mg/kg), 7 sessions of plasmapheresis, antithymocyte globulin (3-5 mg/kg/day for 10 days), rituximab (2 doses at 375 mg/m 2 ), and bortezomib (1 cycle at 1.3 mg/m 2 ), with 2-year graft survival rate after rejection of 90%. [15] Other aggressive salvage therapies include intravenous immunoglobulin [4] and steroid pulse therapy. [16] However, evidence for the most effective treatment for PCAR remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…One may also consider intravenous immunoglobulin, rituximab, or bortezomib in steroid‐resistant cases because of its similar pathogenesis to AMR. Although they may be effective in renal transplant recipients, their efficacy in LTRs has not been shown 1,8 . In terms of outcomes, comparing PCAR with recurrent AIH, there are similar rates of progressive fibrosis and cirrhosis with slightly lower rates of retransplantation in PCAR (23%) 9 compared with recurrent AIH (Table 2).…”
Section: Managementmentioning
confidence: 99%